Technical Perspective on Using Information Demand Pattern in a Collaborative Recommendation System for Improving E-Mail Communication - Dirk Stamer (Complex Systems Informatics and Modeling Quarterly, 2015)
Today e-mail communication information is widely used in organizations to distribute information. The increasing volume of received e-mails hinders an efficient work. It becomes more and more difficult to identify relevant e-mails inside this enormous volume of information. This work presents a solution in a multi-user environment by improving an established e-mail client extension based on information demand pattern with a recommendation system. The contributions of this work are (1) the concept and implementation of the solution for a single-user environment using information demand pattern, (2) the concept and architecture to use the solution in a multi-user environment (3) a detailed technical description about the proposed solutions.